Nitric oxide controls shoot meristem activity via regulation of DNA methylation - Zeng, Jian; Zhao, Xin’Ai; Liang, Zhe; Hidalgo, Inés; Gebert, Michael; Fan, Pengfei; Wenzl, Christian; Gornik, Sebastian G.; Lohmann, Jan U. (Nature Communications, 2023)
Despite the importance of Nitric Oxide (NO) as signaling molecule in both plant and animal development, the regulatory mechanisms downstream of NO remain largely unclear. Here, we show that NO is involved in Arabidopsis shoot stem cell control via modifying expression and activity of ARGONAUTE 4 (AGO4), a core component of the RNA-directed DNA Methylation (RdDM) pathway. Mutations in components of the RdDM pathway cause meristematic defects, and reduce responses of the stem cell system to NO signaling. Importantly, we find that the stem cell inducing WUSCHEL transcription factor directly interacts with AGO4 in a NO dependent manner, explaining how these two signaling systems may converge to modify DNA methylation patterns. Taken together, our results reveal that NO signaling plays an important role in controlling plant stem cell homeostasis via the regulation of de novo DNA methylation.